KINERJA APARATUR PENGELOLAAN DANA DESA (Studi pada Desa di Kecamatan Madat Kabupaten Aceh Timur) - sri Wahyuni; Muhammad Salman; Iqlima Azhar (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2024)
This study aims to determine the effect of Budget Participation, Budget Evaluation and clarity of Village Fund Budget Goals on the Performance of Village Fund Management Apparatus in the Village of Madat District, East Aceh Regency. This study uses quantitative methods using data obtained from questionnaires and measured using an Ordinal scale. The population in this study were all village officials in Madat sub-district as many as 15 villages. This study used purposive sampling technique, namely selecting samples according to certain criteria so that the sample in this study amounted to 60 respondents consisting of village heads, village secretaries, village treasurers and village consultative bodies (BPD). The data analysis methods used in the study were Validity and Reliability Test, Descriptive Statistics, Classical Assumption Test, multiple linear regression, t test, F test, and Coefficient of Determination. For data analysis using SPSS software. The results of this study indicate that Budget Participation, Budget Evaluation, clarity of Budget Objectives have a positive and significant effect on the Performance of the Village Fund Management Apparatus, both partially and simultaneously.